MORAL VALUES IN ANDREA HIRATA’S NOVEL AYAH - Kandri Kandri; Jumino Suhadi; M. Manugeren (Universitas Islam Sumatera Utara (UISU), 2018)
The research deals with moral values. Moral values are the standards of good and evil, which govern an individual’s behavior and choices. Individual’s morals may derive from society and government, religion, or self. When moral values derive from society and government they, of necessity, may change as the laws and morals of the society change. (Harris, 2012). There are two points of moral values analyzed in the novel. The first is hard work and the second is self-confidence and both are depicted through the words and actions of the major characters. Hard work is the key to success. Hard work always pays off. Hard work can turn sludge into gold. Hard work starts from where people stop looking for alternatives. (Tollander, 2011); the second is self-confidence, a belief in one’s own ability when doing anything, by viewing things positively and realistically (Albert, 2010). The research is conducted by descriptive qualitative method proposed by Creswell (2010). The results show that there are two points of moral values in the novel. The first is hard work and the second is self-confidence and both of the points are described by the major characters.